Karakteristik Pembakaran CH4 Dengan Penambahan Co2 Pada Model Helle- Shaw Cell Pada Penyalaan Bawah - Uwar, Nur Aini; Wardana, ING; Widhiyanuriyawan, Denny (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Along with the development of industrial technologies is rapidly increasing the demand for renewable energy sources becomes a very important consideration. One of the alternative energy is now being developed is the energy derived from organic materials, this is because the organic compounds are classified as renewable energy. One energy technology in accordance with the requirements of the biogas technology. If biogas is purified or cleaned of impurities in this case CO2 is good, he would have the same characteristics as natural gas. How big is the influence of CO2 on heating value (heat) in the combustion process it is necessary to an investigation. one by looking at the characteristics of combustion, both the pattern and pace of rambatnya. Combustor used in this study is a model of Helle-shaw cell measuring 50 x 20 x 1 cm. Variation of the mixture used is the ratio 7,5:1 to 10: 1 with the addition of 10% 20%, 30% CO2. Performed on the ignition of ignition. Observation of the shape and rate of flame propagation is done using a high speed camera. The results showed that the ratio of 7,5:1 to 10: 1 blue color of the flame and the flame propagation speed greater penembahan but with 10% CO2 20%, 30% color changing flame reddish yellow which indicates incomplete combustion occurs, and the smaller the rate of flame propagation. This is influenced by the presence of buoyancy forces generated by the combustion.Keywords: energy, gas methane (CH4), CO2, the rate of propagation of flame